Developing Speaking Material Based on Essential Basic Competencies at Muhammadiyah 1 High School Yogyakarta - Adam Al Hakim; Bambang Widi Pratolo; Surono; Ali Zuraina (Teaching English as a Foreign Language Journal, 2022)
Abstract: The objectives of this research are to find out the students’ needs of using material at SMA Muhammadiyah 1 Yogyakarta toward English speaking material due to Covid-19 disease, to find out teachers’ needs towards English speaking material, and to find out the development of English speaking material based on essential basic competencies.This research employs Research and Development. The population was all XI students at SMA Muhammadiyah 1 Yogyakarta and the sample was chosen purposively only 35 students of class XI MIPA 8. The data were gathered through interviews with teachers to find out the existence of the use of English speaking materials. In addition, researchers have also distributed questionnaires to students of class XI MIPA 8 to find out the students' need for appropriate modules to improve speaking skills. The data was analyzed by based on the theme of the research questions.The results of this study indicate that the existing material is in line with the pandemic conditions, such as the module design being attractive, the content in the module in line with the latest syllabus (essential basic competencies), and the module being converted into the online form, thus students can study anywhere and anytime. The students' need for the material developed showed very varied results. As for the module development process, the researcher follows the stages under the Research and Development method.